Sustainable Biofuel Production through Biomass Conversion - Dr. M. Muthukumaran; K. Gowtham; P.Vignesh; C. Amalraj; R. Subash (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The growing demand for renewable energy has sparked significant interest in biomass as a sustainable feedstock for biofuel production. This study explores the conversion of biomass into biofuel through the pyrolysis process, utilizing onion shell powder as the primary feedstock. Pyrolysis, a thermochemical process performed in the absence of oxygen, yields bio-oil, biochar, and syngas, which can serve as viable alternative energy sources. To improve the efficiency of biofuel production, a catalyst is employed to optimize reaction conditions, maximize bio-oil yield, and enhance fuel properties. Key fuel properties of the biofuel, such as density, viscosity, flash point, fire point, and calorific value, are evaluated to assess its quality and performance. These parameters are crucial for determining the combustion characteristics, safety, and efficiency of the produced biofuel. A comparative analysis with conventional fossil fuels is conducted to evaluate energy output, ignition properties, and environmental impact. The results provide valuable insights into the viability of biofuels as a sustainable energy source and highlight areas for further optimization in industrial applications. This research also contributes to the growing body of knowledge on the development of cleaner, more efficient biofuels as an alternative to fossil fuels. The bio-oil is assessed for its calorific value and chemical composition, while biochar and syngas are examined for potential applications. By using onion shell powder, an agricultural waste product, this study not only promotes waste valorization but also advances sustainability. The findings emphasize that optimized catalytic pyrolysis can significantly enhance biofuel yield and properties, offering an environmentally friendly alternative to traditional fossil fuels.